The Integration of Values and Science Education in Learning to Strengthen the Existence of Muslims in the Industrial Age 4.0 - Kristiwati, Heni (International Conference of Moslem Society, 2019)
Such integration is bringing together various sciences into one that is mutually supportive, balanced and sustainable to compile learning. By providing integration in the fields of education, economics or whatever, it is hoped that there is no knowledge that groups knowledge itself, because integrating knowledge with each other will be a sharp unit in the educational process that leads to learning. The reality of integrating value education with science in learning is still experiencing some problems related to the lack of understanding on how to combine values and science education in learning. Science will complement our interactions in society. Both must be interrelated. For this reason, the rapid flow of world development in terms of technology and information has led to the birth of the industrial revolution era 4.0 which exists when the large technology occurs by significant socio-economic and cultural changes. The existence of an industrial revolution 4.0 brings up to the phenomenon of new industries which result is disruptive innovation. With the current industrial revolution that has placed on all aspects, especially in the aspect of education, education is intended to humanize humans. The methods of integration include five models, namely the value-planting approach, cognitive development approach, value analysis approach, value clarification approach and action learning approach.